The Implementation of the Mobile-Assisted Language Learning (MALL) Cake Application in Supporting EFL Students' Speaking Practice - Muh. Rusyaid; Nurdin Noni; Muhammad Tahir; St. Nur Aima Fatima (Jurnal IPTEK Bagi Masyarakat, 2026)
This study investigated the implementation of the Mobile-Assisted Language Learning (MALL) Cake application in supporting EFL students' speaking practice at Al Ikhlas Islamic Boarding School Ujung Bone. An explanatory sequential mixed-methods design was used. Quantitative data were collected through a questionnaire administered to 35 tenth-grade students who had used the Cake application, followed by semi-structured interviews with seven selected participants. The findings indicate that students perceived the application as a useful tool for speaking practice because it increased motivation and self-confidence, reduced speaking anxiety, and encouraged positive attitudes toward technology-assisted language learning. Students also valued its engaging materials, interactive speaking activities, pronunciation feedback, and flexible access, which supported more frequent practice beyond the classroom. The study concludes that the Cake application can serve as a complementary MALL tool for supporting speaking practice in EFL contexts by promoting motivation, confidence, and active engagement. However, the findings represent students’ perceptions rather than objectively measured improvements in speaking performance.